Dynamics of Phytoplankton Communities and Their Characteristics of Realized Niches in a Drinking Reservoir - Shuhua Wang; Xujun Liang; Shanshan Zhang; Mingjiang Cai; Zhangxian Xie; Lizhen Lin; Zhenguo Chen; Yiyong Rao; Yanping Zhong (Ecology and Evolution, 2025)
ABSTRACT Realized niches are crucial in defining their optimal conditions and serve as valuable tools for predicting the phytoplankton dynamics in relation to eutrophication, climate change, and harmful phytoplankton blooms. However, previous studies have largely focused on marine ecosystems, leaving freshwater systems less studied. In this study, we elucidate the patterns of phytoplankton community succession based on their niche characteristics in the Shanmei (SM) Reservoir, a drinking water source in Quanzhou, Fujian Province. Additionally, variations in phytoplankton were mainly explained by their realized niche. In the SM Reservoir, total chlorophyll a concentrations ranged from 252 to 24,008 ng/L. The phytoplankton community was dominated by Chlorophyta and Cyanophyta, which consisted mostly of Pseudanabaena and Microcystis, especially in summer. This dominance was attributed to their wide niche breadth and high mean niche for temperature, nitrogen, and dissolved reactive phosphorus. On the other hand, Cryptophyta and Bacillariophyta reached higher concentrations in autumn and winter, linked to their low mean temperature niches. Under the multiple pressures of climate change and anthropogenic activities, Chlorophyta and Cyanophyta are likely to thrive in environments characterized by rising water temperatures and elevated nutrient concentrations. This is particularly true for buoyant cyanobacteria such as Pseudanabaena, which are well‐suited to the stratified water layers induced by higher water temperatures. Therefore, incorporating niche characteristics of harmful bloom‐forming species would contribute to the prevention and management of harmful phytoplankton blooms, ultimately improving the safety of drinking water.